The Potential of Sorghum Water Extract as Bioherbicide Under Different Varieties and Water Stresses: - Susilo, Edi; Setyowati, Nanik; Pujiwati, Hesti (International Journal of Integrative Sciences, 2024)
The potential of sorghum plants to produce allelopathy is determined by the variety and the level of stress it receives. This study aimed to obtain information on the potential of sorghum water extract as a bioherbicide due to water stress treatment with different varieties. This study used a one-factor group randomized design. The extract source treatments were as follows: Super 2 + watering once every 1, 2, and 3 days; Suri 4 + watering once every 1, 2, and 3 days; Bioguma + watering once every 1, 2, and 3 days and control. Bioassay method experiments in petri dishes. Each petri dish was given 10 ml of aqueous extract with a concentration of 5%. A total of 25 sorghum seeds were planted and incubated for three days. The results showed that all water extracts from sorghum varieties Super 2, Suri 4, and Bioguma, combined with all water stresses, could inhibit the growth of the test plants. However, Super 2 + once every 5 days inhibited the test plants the most compared to the other treatments. Therefore, these sorghum water extracts have the potential to be used as bioherbicides to control weeds